i Inventarisasi Koleksi Lontar Milik Masyarakat Bali Oleh Musium Gedong Kirtya: inventarisasi lontar masyarakat - damayanti, teriana (ACARYA PUSTAKA, 2024)
Lontar is one of the written cultural heritages with historical, educational, and spiritualvalue for the Balinese people. However, its preservation faces increasing challenges due toaging, environmental conditions, and the younger generation's lack of awareness. The GedongKirtya Museum plays a crucial role in safeguarding, documenting, and inventorying lontarcollections to ensure their preservation. This study aims to examine the process of inventoryingcommunity-owned lontar carried out by the Gedong Kirtya Museum and to identify thechallenges faced in its implementation. This research employs a qualitative descriptive methodwith data collection techniques including observation, interviews, and document studies. Theresearch informants consist of Gedong Kirtya Museum managers, library staff, and communitylontar owners. The findings reveal that the inventory process includes identification,documentation, conservation, and digitization of lontar manuscripts. The main challengesencountered in the inventory process include environmental factors such as humidity and pestinfestations, limited human resources for preservation efforts, and low public awareness of theimportance of lontar as a cultural heritage.Keywords: Inventory, Lontar, Cultural Preservation, Gedong Kirtya Museum